2014
DOI: 10.2147/dddt.s63096
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoinformatics elucidation of potential drug targets against migraine to target ion channel protein KCNK18

Abstract: Migraine, a complex debilitating neurological disorder is strongly associated with potassium channel subfamily K member 18 (KCNK18). Research has emphasized that high levels of KCNK18 may be responsible for improper functioning of neurotransmitters, resulting in neurological disorders like migraine. In the present study, a hybrid approach of molecular docking and virtual screening were followed by pharmacophore identification and structure modeling. Screening was performed using a two-dimensional similarity se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Our study supports the notion that TRESK channels are essentially involved in pain perception in general especially under inflammatory conditions. Recently diverse drug screening approaches identified new compounds that specifically bind and modulate the activity of TRESK channels 49 50 51 suggesting TRESK to represent a promising target molecule for the treatment of severe pain disorders such as migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports the notion that TRESK channels are essentially involved in pain perception in general especially under inflammatory conditions. Recently diverse drug screening approaches identified new compounds that specifically bind and modulate the activity of TRESK channels 49 50 51 suggesting TRESK to represent a promising target molecule for the treatment of severe pain disorders such as migraine.…”
Section: Discussionmentioning
confidence: 99%
“…These residues are located near the extracellular face of TMs 1, 2 and 4 based on a putative structural model of the TRESK channel. Additionally, these authors suggested several compounds, which might bind to this site and be useful in the treatment of migraine [90]. Whilst this approach provides an interesting potential start point for further experimental studies, it is not known whether the suggested compounds will indeed bind to the TRESK channel nor, if they do, whether they will enhance channel activity, block channel activity or have no effect.…”
Section: Pharmacological Enhancement Of Tresk Channel Activitymentioning
confidence: 99%
“…Activation of trigeminal nociceptors innervating the dural meninges likely underlies the headache phase of migraine (Weir and Cader, 2011), offering a plausible locus of action of the mutation due to the enrichment of TRESK in these afferents (Lafrenière et al, 2010). Such data is leading to increased efforts to target channel activity as an analgesic strategy (Wright et al, 2013; Bruner et al, 2014; Sehgal et al, 2014; Mathie and Veale, 2015).…”
Section: Introductionmentioning
confidence: 99%